Kecenderungan Bahasa Arab Dalam Penamaan Anak Melayu Di Pelembang (Taqdir, 2025)
This research is motivated by the issue of shifting naming traditions among Malay children in Palembang. In the past, children's names were predominantly Islamic or Arabic in nature, but there has been a noticeable trend toward using more modern or contemporary names. The objectives of this study are as follows. First, to examine hereditary tendencies in the naming of Malay children in Palembang. Second, to analyze the influence of the Arabic language in these naming practices. Third, to identify modern trends in the naming of Malay children in Palembang. The research employs a qualitative methodology with an onomastic approach. Data were collected through interviews and documentation. For data analysis, the study utilizes the qualitative analysis model developed by Strauss and Corbin (grounded theory). The findings reveal three main tendencies in the naming practices of Malay children in Palembang: (1) A hereditary tendency, where names such as Msy, Mgs, Nyayu, and Kgs are used, reflecting a sense of identity and continuity; (2) An inclination toward Arabic names, often inspired by significant events or months in the Islamic calendar, serving as a form of cultural preservation; and (3) A modern and Western influence, indicating a shift in naming conventions.